Phenolic metabolites of anthocyanins following a dietary intervention study in post‐menopausal women. Issue 3 (30th October 2013) - de, Rachel M.; Cassidy, Aedín; Curtis, Peter; Kay, Colin D.
<x xml:space="preserve">Abstract</x> Scope Numerous studies feeding anthocyanin‐rich foods report limited bioavailability of the parent anthocyanins. The present study explores the identity and concentration of the phenolic metabolites of anthocyanins in humans. Methods and results Anthocyanin metabolites were quantified in samples collected from a previously conducted 12‐wk elderberry intervention study in healthy post‐menopausal women. Individual 1‐, 2‐ and 3‐h post‐bolus urine samples and pooled plasma samples following acute (single bolus) and chronic (12‐wk supplementation) anthocyanin consumption (500 mg/day) were analysed using HPLC‐ESI‐MS/MS. Twenty‐eight anthocyanin metabolites were identified in urine and 21 in plasma (including sulfates of vanillic, protocatechuic and benzoic acid). Phenolic metabolites reached peak concentrations of 1237 nM in plasma, while anthocyanin conjugates only reached concentrations of 34 nM. Similarly, in urine, phenolic metabolites were detected at concentrations of 33 185 ± 2549 nM/mM creatinine, while anthocyanin conjugates reached concentrations of 548 ± 219 nM/mM creatinine. There was no evidence that chronic exposure had any impact on either the profile or quantity of metabolites recovered relative to acute exposure. Conclusion An extensive range of phenolic metabolites of anthocyanin was identified following elderberry consumption in humans, including 11 novel metabolites, which were identified at much higher concentrations than their parent compounds.